Representational meanings of gender stereotyped professional occupation images in selected Malaysian English language textbooks - Chairozila Mohd Shamsuddin,; Bahiyah Abdul Hamid, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The main objective of this study is to examine and reveal images of gender-stereotyped occupations from primary school English textbooks and uncover gendered attributes from these images. Images in the textbooks are investigated based on how representational meanings reveal agentic and communal qualities. Images were analysed through identifying patterns and relationships of images to attributes from Social Role Theory. Stereotyped images were identified through links and associations from Atlas.ti software that connected images with characteristics and meanings. This study found 126 images represented in professional occupations and 81 images represented in non-professional occupations. Results showed that occupational images of males were linked to more self-assertive and agentic qualities while females were portrayed with more caring, communal qualities. Social semiotic analysis revealed that more males were shown as professionals such as architects, and doctors whereas females are more portrayed with professional occupations such as nurses and teachers, and non-professional males were also included with agentic qualities, portrayed by farmers and firefighters. This study asserts that a more gender-equitable solution would be to give children a wider range of portrayals of men and women in order to communicate gender norms to children. Parents, caretakers, teachers and schools also have responsibilities towards boys and girls in that they ensure learning happens in an environment that they do not give out messages, subliminal or otherwise that there are subjects that are only particular to boys and only particular to girls. Apart from teachers, this is particularly true also for parents, family members and caretakers where they may be directly influencing children who are in their care towards gender stereotypical subject choice all throughout the children’s schooling life in the home environment. Furthermore, parents, teachers and schools must cooperate together to encourage boys and girls at an early age to be interested in non-stereotypical options in subject choice.